The Effect of Trade Openness and Investment Realization on Inclusive Economic Growth in Cities and Districts of East Java in 2015-2019 - Farida Rahmawati; Silvi Dewi Purwanti; Nadiah Ramadhani (Nusantara Science and Technology Proceedings, 2020)
Economic growth is hoped to have a positive impact and also increase the welfare of the community. a good inclusive economic growth requires a study on this matter, it can be started by looking at what factors can fulfill inclusive economic growth. So, this research aims to know the inclusive economic growth of cities and districts in East Java in 2015-2019 and to look at the factors that can influence the achievement of inclusive economic growth. The research method used is the calculation of inclusive growth created by UNDP and panel data linear regression analysis. In 2019, all regions at the level were filled by districts, while the city was still at the intermediate level. The results of the regression analysis show that trade openness and investment realization affect the inclusive economic growth of cities and districts in East Java in 2015-2019.